2011
DOI: 10.1111/j.1601-5223.2011.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of supportive stockings on native pikeperch populations in boreal lakes - three cases, three different outcomes

Abstract: The genetic consequences and gene flow of pikeperch (Sander lucioperca) stocking were assessed in three boreal lakes based on admixture model analysis and comparison of the pre- and post-release patterns of genetic variability at 9 DNA microsatellite loci in the recipient populations. In two out of the three cases, the releases of fish from foreign populations caused significant changes in the genetic structure of the recipient population. The largest changes were observed in Lake Oulujärvi, where the post-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Strong evidence, that this also holds true for zander, is provided in a recent work of Salminen et al. (). Studying three lakes, they found low replacement of native gene pools, when natural recruitment of zander was high, but they observed extended replacement and high levels of admixture, when self‐recruitment was low.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Strong evidence, that this also holds true for zander, is provided in a recent work of Salminen et al. (). Studying three lakes, they found low replacement of native gene pools, when natural recruitment of zander was high, but they observed extended replacement and high levels of admixture, when self‐recruitment was low.…”
Section: Discussionmentioning
confidence: 79%
“…However, more and more evidence is accumulating that stocking in the presence of self-sustaining fish stocks is rarely successful in a range of freshwater fish species (vendace Coregonus albula in Mehner et al 2010;pike in Larsen et al 2005; charr Salvelinus alpinus in Englbrecht et al 2002;trout in Hansen 2002). Strong evidence, that this also holds true for zander, is provided in a recent work of Salminen et al (2012). Studying three lakes, they found low replacement of native gene pools, when natural recruitment of zander was high, but they observed extended replacement and high levels of admixture, when self-recruitment was low.…”
Section: An Alternative Explanation and Concluding Remarksmentioning
confidence: 91%
“…Small‐scale introductions may have been made also in Tuhkajoki, which could explain the presence of hatchery genotypes in this population. Several studies have shown that introgression from hatchery stocks to wild fish populations occurs especially when the number of stocked fish is high compared to the number of wild individuals (Hansen, ; Hindar, Ryman, & Utter, ; Ozerov et al, ; Salminen, Koljonen, Säisä, & Ruuhijarvi, ), as is the case in Lake Oulujärvi area. Further, introgression from hatchery‐reared fish can occur at sites distantly located to the stocking location (Vasemägi, Gross, Paaver, Koljonen, & Nilsson, ; Finnegan & Stevens ).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the studied wild populations appeared to be an isolated unit with very limited gene flow from the other rivers or from the hatchery-reared fish, which is in line with their historical and present-day connectivity. Although (Hansen, 2002;Hindar, Ryman, & Utter, 1991;Ozerov et al, 2016;Salminen, Koljonen, Säisä, & Ruuhijarvi, 2012), as is the case in Lake Oulujärvi area. Further, introgression from hatchery-reared fish can occur at sites distantly located to the stocking location (Vasemägi, Gross, Paaver, Koljonen, & Nilsson, 2005;Finnegan & Stevens 2008).…”
Section: Implications For Conservation and Management Of Brown Troutmentioning
confidence: 92%
“…These enhancements have included releases of artificially reared stocks or escapes of large numbers of individuals characterized by lower fitness (Satake and Araki 2011;Baskett et al 2013;Milot et al 2013;Naish et al 2013) and lower genetic diversity have been reported for some species, including Adriatic sturgeon (Boscari and Congiu 2014), Korean starry flounder ) and black sea bream in Japan (Blanco Gonzalez and Umino 2009). Other effects have been introductions of nonindigenous populations, such as salmon in Poland (Poćwierz-Kotus et al 2015a;Bernaś et al 2016); or alien populations of the same species and their subsequent hybridization a Corresponding author: rwenne@iopan.gda.pl with local native populations, as with salmon and brown trout in Bulgaria (Chelenkova et al 2012), Norway (Thaulow et al 2012), Hungary (Horváth et al 2013) and in Spain (Madeira et al 2005), pikeperch in Finland (Salminen et al 2012); unintentional escapes from hatcheries as red sea bream in Japan (Blanco Gonzalez et al 2015), salmon in Norway (Liu et al 2013) and Canada (Fraser et al 2008). Accidental or deliberate introductions of exotic and invasive species to new environments, often beneficial economically, causes distortions in the functioning of local ecosystems and can threaten native populations of fish and shellfish, as in the case of brown trout in Japan (Hasegawa and Maekawa 2008), Patagonia (Vigilano et al 2007;Young et al 2010) and in North America (Turek et al 2016), mussel Mytilus in Europe and South Africa (Kijewski et al 2009;McQuaid et al 2015 and oyster Crassostrea gigas (Carlton 1979;Meehan et al 1989;Miller et al 2012;Lallias et al 2015).…”
Section: Introductionmentioning
confidence: 99%